The Simulation of Radiation Shielding Made of Portland Material in a 230 MeV 300 NA Cyclotron Room for Proton Therapy Facility Using PHITS Code System - Damar Adhiwidya Suyanto; Aditya Tri Oktaviana; Yohannes Sardjono; Gede Sutresna Wijaya; Isman Mulyadi Triatmoko (Universitas Proklamasi 45, 2025)
This study investigates the effectiveness of radiation shielding made from Portland material in a 230 MeV, 300 NA cyclotron room for a proton therapy facility. Proton therapy is an advanced treatment method for cancer that uses protons to irradiate tumors with high precision. However, the high energy of protons requires effective shielding to protect the surrounding environment and personnel from radiation exposure. In this research, the radiation shielding performance of Portland material was evaluated using the PHITS (Particle and Heavy Ion Transport System) version 3.351 simulation software. The study focuses on assessing the attenuation of radiation within the cyclotron room under various operational conditions. The results from PHITS simulations provide insights into the potential of Portland material in reducing radiation levels in proton therapy rooms, contributing to the safety and efficiency of such facilities. This analysis is essential for optimizing shielding design.